EFEKTIVITAS DOSIS HORMON TIROKSIN YANG BERBEDA TERHADAP KINERJA PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN DEPIK (Rasbora tawarensis) - Putro, Riski Nogo; Komariyah, Siti; Febri, Suri Purnama; Hasir, Iwan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Depik fish is a fish which is one of the endemic species in Lake Laut Tawar, Central Aceh Regency. Typical fish of the Gayo community which is currently being developed for domestication. However, from the results of several studies, the growth of depik fish is relatively slow, so it needs to be increased. One way to accelerate the growth of depik fish is by hormonal induction, through immersion in the hormone thyroxine with different doses. The aim of this research is to evaluate the growth performance and survival of depik fish soaked in thyroxine hormone with different doses of thyroxine hormone. This research was carried out at the Lukup Badak Fish Seed Center (BBI), Central Aceh using a completely randomized design (CRD) experimental method with four treatments and three repetitions. The treatments in this research were different durations of immersion in the thyroxine hormone, namely: no dose (P0), 0.05 mg/ liter (P1), 0.1 mg/ liter (P2), and 0.15 mg/ liter (P3). Meanwhile, the duration of the thyroxine hormone soaking used is 24 hours. Rearing of fish seeds is carried out using an Aquarium measuring 30 cm long, 20 cm wide and 25 cm high according to the treatment, for 28 days with a stocking density of 20 fish/container. This study concluded that different doses of the thyroxine hormone in Depik fish fry gave the highest growth in the treatment dose of 0.15 mg/liter, while the lowest growth was in the control treatment (no dose).